Testing of Deliver Active Power for Operation Sub–Sync and Super-Sync on Doubly Fed Induction Generator Applied in Wind Turbine - Mutiar; Siswandi; Yessi Marniati; Nurhaida; Dezetty Monika (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
Technology developments related to the renewable energy industry are increasing, one example of wind power generation technology which has several relationship configurations with generator. This system configuration is known a wind generator with a DFIG (Double Fed Induction Generator). This system can supply active power from the induction generator stator connected directly to the network while the rotor is connected to the network through a back to back converter. The operation of the double feeder induction generator (DFIG) consists of two conditions, the first condition is super-synchronous where power will be transmitted from the rotor through the converter to the network and the second condition is sub-synchronous where the rotor will absorb power from the network through the converter. This research was conducted to determine the active power distribution in two operating conditions of a double feeder induction generator. Generator power delivery increases for sub-synchronous and super-synchronous operation when active MSC increases from 10% to 60% and generator speed is constant. For a changing speed and a constant active MSC, constant power distribution from the generator (PDFIG) is obtained.